Safety and immunogenicity of 17DD attenuated yellow fever vaccine in howler monkeys (Alouatta spp.). Issue 1 (20th November 2020) - Tavares da Silva Fernandes, André; Moreira, Silvia Bahadian; Gaspar, Luciane Pinto; Simões, Marisol; Cajaraville, Ana Carolina dos Reis Albuquerque; Pereira, Renata Carvalho; Gomes, Mariana Pierre de Barros; Linhares, José Henrique Rezende; Santos, Vanessa de Oliveira; Santos, Renata Tourinho; Amorim, Juliana Fernandes; Barros, Tamiris Azamor da Costa; et al.
Abstract: Background: Alouatta spp. are highly susceptible to yellow fever (YF) infection and develop an often fatal disease. The threat posed by an outbreak started in 2016 leads us to investigate vaccination as a potential tool in preventing YF in non‐human primates (NHP). Methods: Susceptible howler monkeys were immunized with three different concentrations of the human Brazilian commercial YF17DD vaccine. Post‐vaccination viremia/RNAemia, immunogenicity, and safety were characterized. Results: The vaccine did not produce YF clinical manifestations in any of the NHPs. After immunization, all animals seroconverted demonstrating the ability of the YF vaccine to induce humoral response in Alouatta species. Conclusions: The present work has demonstrated the safe and immunogenic profile of the existing YF 17DD vaccine in howler monkeys. This knowledge may support further studies with other susceptible monkey species and provide a possible solution for controlling epizootics and preventing the devastation of endangered species.